THE MAIN PROTOCOL AND OTHER IDENTIFIED STRATEGIES TO ADDRESS CLIMATE CHANGE & ITS IMPACT ON HEALTH - Faisal Abass Padder; Asif Bashir; Shabir Ahmad Dar (CV. Radja Publika, 2023)
Climate change is a global crisis that has a direct impact on human health. Rising temperatures, extreme weather events, and changes in precipitation patterns are affecting the health of individuals, communities, and ecosystems worldwide. To address this challenge, a protocol and strategies have been identified that aim to mitigate the impact of climate change on health. The main protocol involves reducing greenhouse gas emissions through the adoption of cleaner and renewable energy sources, improving energy efficiency, and sustainable transport. Other strategies include enhancing public awareness, building climate-resilient communities, promoting sustainable agriculture, and improving health systems' preparedness for climate-related emergencies. Implementation of these measures can help reduce the risk of climate-related health problems such as heat stress, respiratory illnesses, and vector-borne diseases. The protocol and strategies identified provide a roadmap for governments, organizations, and individuals to take action against climate change and protect the health of the planet and its inhabitants.